2017
DOI: 10.5993/ajhb.41.6.11
|View full text |Cite
|
Sign up to set email alerts
|

Household Food Security Discordance Among Latino Adolescents and Parents

Abstract: Discordant reports of Latino household food security suggest the burden of unequal access to sufficient foods may be underestimated. Discordant reports may follow from cultural values that may encourage adolescents to keep hunger from their parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…The use of self-report of child food insecurity experiences is seen as a strength of this study. Child-report of their personal experiences with food insecurity has been shown in the literature to be more representative of their actual experiences and rules out potential biases that may result from parental reporting [15,16,17,18,19]. Sample size for this study was smaller than previous studies and is only locally representative; however, the scale of this study enabled us to control for confounding variables of potential relevance to food insecurity and diet, such as body weight or BMI, which prior studies have not controlled for.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of self-report of child food insecurity experiences is seen as a strength of this study. Child-report of their personal experiences with food insecurity has been shown in the literature to be more representative of their actual experiences and rules out potential biases that may result from parental reporting [15,16,17,18,19]. Sample size for this study was smaller than previous studies and is only locally representative; however, the scale of this study enabled us to control for confounding variables of potential relevance to food insecurity and diet, such as body weight or BMI, which prior studies have not controlled for.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of nearly all previously mentioned studies examining the relationship between food insecurity and dietary quality is the use of parent-reported household food insecurity [3]. Consistently, research has shown that parental report of child-level food insecurity may be unrepresentative of actual child food insecurity experiences and if a parent proxy is used, prevalence of child-level food insecurity may be grossly underestimated [15,16,17,18,19]. The two studies that have used child self-report of their own food security experiences to examine associations between dietary quality and food insecurity have found no association [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Household food security can differentially impact children when compared to adults within the same household, which is often explained as children being protected from the lack of food resources [42,43]. However, we cannot rule out potential bias in parental reporting on children’s experiences [44,45,46]. The strength of agreement between the two classification scales was lower in non-Hispanic Black and Hispanic children and those with lower family income; this may be partly due to higher food insecurity in these subgroups, but also highlights a need for special efforts in assessing food insecurity by race and Hispanic origin and family income.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, food-insecurity assessment is challenging. Neither household food security nor food security among children measures an individual child’s food insecurity, even though a child report can differ from an adult report [44,45,46]. Nonetheless, most large surveys and studies, including NHANES, interview an adult responsible for household food management about the food-security status of household members using the HFSSM.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported notable discordance between reports from parents and children. Previous studies have primarily focused on older child populations (>12 y old) (10–12). Other studies have utilized younger child populations; however, these studies are limited in terms of study sample size (<91 children) (8, 13, 14).…”
Section: Introductionmentioning
confidence: 99%